PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus BRI Kantor Cabang Yogyakarta Mlati) - Feby Hidayati (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of service quality, customer values on customer satisfaction. The population in this study is the savings deposits of retail customers BRI Yogyakarta Branch Office Mlati for 5 years with a balance above Rp 100.000.000.- sampling technique used was accidental sampling method of selecting samples taken from members of the population are chosen by chance fit a particular purpose , The technique of collecting data using questionnaires. The analysis is an inferential analysis path analysis. From the results of the study concluded that: The test results show that Quality of Service positive and significant effect on the Customer Satisfaction although positive and significant effect, but this value is still low. Good service, and as expected foster a sense of satisfaction and confidence of consumers in enjoying the products or services it uses. The test results show that the Customer Value effect on Customer Satisfaction). It means to have a positive and significant influence but this result is lower when compared to the variable quality of service. If more and more customers look sacrifice or service benefits exceed the costs incurred to acquire a service, the higher their perceptions of the value of the service, since they get more than expected, which in turn will produce greater satisfaction.